EAP teachers' knowledge and use of learning-oriented assessment: A cross-contextual study. (February 2022) - Fazel, Ismaeil; Ali, Afiza Mohamad
Abstract: An emerging approach to classroom-based assessment that has gained increasing attention in the past decade is 'learning-oriented assessment', conceptualized as assessment which affords primacy to the learning orientation of classroom assessment, placing particular emphasis on active engagement of learners in assessment and feedback (Carless, 2015; Turner & Purpura, 2015). It is arguably important for EAP practitioners to be informed of and implement innovative approaches to assessment, including learning-oriented assessment. This paper reports on a qualitative study exploring EAP teachers' knowledge and use of learning-oriented assessment (Carless, 2015; Turner & Purpura, 2015) in the contexts of higher education in Canada and Malaysia. After presenting and discussing the comparative findings from the two contexts, we will provide suggestions and implications for EAP teacher training and professional development, which can in turn help inform initiatives to cultivate and enhance EAP teacher assessment literacy across these two contexts and beyond.